Internalization of components of the host cell plasma membrane during infection by Trypanosoma cruzi - Carvalho TMU; De Souza W; Coimbra ES (Memorias do Instituto Oswaldo Cruz, 1999)
Epimastigote and trypomastigote forms of Trypanosoma cruzi attach to the macrophage surface and are internalized with the formation of a membrane bounded vacuole, known as the parasitophorous vacuole (PV). In order to determine if components of the host cell membrane are internalized during formation of the PV we labeled the macrophage surface with fluorescent probes for proteins, lipids and sialic acid residues and then allowed the labeled cells to interact with the parasites. The interaction process was interrupted after 1 hr at 37ºC and the distribution of the probes analyzed by confocal laser scanning microscopy. During attachment of the parasites to the macrophage surface an intense labeling of the attachment regions was observed. Subsequently labeling of the membrane lining the parasitophorous vacuole containing epimastigote and trypomastigote forms was seen. Labeling was not uniform, with regions of intense and light or no labeling. The results obtained show that host cell membrane lipids, proteins and sialoglycoconjugates contribute to the formation of the membrane lining the PV containing epimastigote and trypomastigote T. cruzi forms. Lysosomes of the host cell may participate in the process of PV membrane formation.